Menguji Loyalitas Pelanggan Restoran - Sabar Sabar (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2018)
This study aims to examine the effect of service quality on satisfaction and its impact on the restaurant's ability to build customer loyalty. The sampling method used was accidental sampling. The analysis technique used was SEM PLS. The results showed that the quality of service had an impact on satisfaction which led to an increase in restaurant customer loyalty. Managerial implications of research results should be that managers or restaurant owners could improve service quality through reliability, responsiveness, assurance, empathy, tangible so that customer satisfaction increases so that it had an impact on customer loyalty.